2020
DOI: 10.1590/0037-8682-0377-2019
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the risk of snakebites incidence due to changes in humidity levels: A time series study in four municipalities of the state of Rondônia

Abstract: Introduction: Snakebites represent a serious global public health problem, especially in tropical countries. In Brazil, the incidence of snakebites ranges from 19 to 22 thousand cases per 100000 persons annually. The state of Rondônia, in particular, has had an increasing incidence of snakebites. Methods: A retrospective cross-sectional study on snakebites was conducted from January 2007 to December 2018. Brazil's Information System for Notifiable Diseases was queried for all snakebites reported in Porto Velho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
3
16
0
1
Order By: Relevance
“…The snakebites analyzed in the present study had a greater occurrence during the rainy season (64,24%) and the historical series (2009-2018) was statistically associated with the low seasonal river levels and rainfall, thus confirming the observations of other studies 3 , 6 , 8 , 11 , 22 - 24 . This predominance of snakebites in the wettest months is probably related to the increase in snake activity in this period, due to the greater availability of prey and reproductive activities 25 , 26 .…”
Section: Discussionsupporting
confidence: 91%
“…The snakebites analyzed in the present study had a greater occurrence during the rainy season (64,24%) and the historical series (2009-2018) was statistically associated with the low seasonal river levels and rainfall, thus confirming the observations of other studies 3 , 6 , 8 , 11 , 22 - 24 . This predominance of snakebites in the wettest months is probably related to the increase in snake activity in this period, due to the greater availability of prey and reproductive activities 25 , 26 .…”
Section: Discussionsupporting
confidence: 91%
“…One study in Thailand mentions the increased incidence of snakebite in children during floods ( Laohawiriyakamol et al, 2011 ). In Brazil a time-series study analyzing rainfall and humidity levels over years concluded that increased humidity (rather than rainfall) is related to increased snakebite yearly admissions ( Ferreira et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such geographical link with diseases leads to the challenge of spatial mapping of disease transmission which overcame through the branches of biodiversity science—ecology and biogeography. Such approach of ecological and biogeographical modelling can be seen from various studies on disease transmission risks mapping, for example, Arboleda et al ( 2009 ), Deka and Morshed ( 2018 ), Ferreira et al ( 2020 ), Holt et al ( 2009 ), Mweya et al ( 2013 ), Nakazawa et al ( 2013 ), Reeves et al ( 2015 ), Samy et al ( 2014 ), Qian et al ( 2014 ), Zhao et al ( 2016 ), Zhu et al ( 2017 ).…”
Section: Infectious Diseases Modellingmentioning
confidence: 99%